Behind those bars a qualitative study on the patterns and the trends in the adaptation process of student detainees in the Quezon City Jail - Diaz, Allan Anthony E.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
This qualitative study explored the adaptation process of student detainees in the Quezon City Jail. Specifically, the study looked at the detainees sources of stress and their coping styles as revealed through their communication patterns, the types of activities they engage in and the different support groups. Gerhardt's Stress and Coping Framework. Lazarus' Cognitive-Psychological Model of Stress, Altman and Taylor's Social Penetration Theory and Gudykunst Anxiety/Uncertainty Management Theory were integrated to come up with a suitable model that will correspond with the different concepts included in the study. The sources of stress were identified at the physical, emotional and social levels. At the physical level, health and hygiene were important to the detainees. Homesickness is typical among respondents and is a primary source of stress. Through support groups, the inmates were able to cope better with stress they experience inside the jail. The study was able to evaluate conditions inside the Quezon City Jail that contribute to the stress that makes their stay unpleasant. The findings of this research can help prison administrations to improve their facilities and the basic sources they give to inmates. The researcher recommends the inclusion of Key-Informant Interviews of prison officials for future studies of this nature. Interviews with psychologists are also pertinent as these can provide a better understanding of the adaptation process of student detainees.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Juvenile detention homes -- Philippines; Correctional psychology -- Philippines